Numerical modeling of AZTS as buffer layer in CZTS solar cells with back surface field for the improvement of cell performance. (1st January 2022) - Jamil, M.; Amami, Mongi; Ali, A.; Mahmood, K.; Amin, N.
Highlights: Modeling of CZTS solar cells. AZTS as buffer layer. Effect of various parameters. Efficiency enhanced. Abstract: This paper presents the use of AZTS, a non-toxic and earth abundant material as buffer layer in CZTS solar cells due to its good lattice match. We have performed simulation on the experimentally fabricated AZTS/CZTS hetero-junction device by adding CZTS as back surface field (BSF) layer. In this work, first we have reconstructed the AZTS/CZTS experimentally designed solar cell then BSF layer is added to boost the solar cell performance in SCAPS simulator. Several parametersof AZTS buffer layer such as generation/recombination rate and doping concentration are varied during simulationto enhance the performance of investigated solar cells structures. It has been noticed that addition ofBSF layer increasesthe efficiency of AZTS/CZTS solar cell from 4.51% to 5.05% along with improvement of both Voc and FF.